Physic nut, Jatropha curcas L. - Heller, J. (1996)
This tropical crop is native to Mexico and Central America, but is cultivated in many other Latin American, Asian and African countries as a hedge. It has become of interest to various development agencies because it adapts well to semiarid marginal sites, its oil can be processed for use as a diesel fuel and it can be used for erosion control.This monograph has chapters covering the following aspects of J. curcas: names of the species and taxonomy; botanical description; origin and centre of diversity; properties (toxicology); uses (whole plant and food/fodder, medicine, plant protectant and molluscicide, technical uses, diesel fuel and other uses); genetic resources (existing genetic variation, conservation); breeding (objectives, method and selection based on provenance trials); production areas; ecology; agronomy (growth and development, propagation methods and pests and diseases); limitations of the crop; prospects; and research needs.There are appendices listing (I) research contacts, centres of crop research, breeding and plant genetic resources of physic nut and (II) publications of Proyecto Biomasa, DINOT/UNI, Nicaragua. (Abstract © CAB ABSTRACTS, CAB International)